2018
DOI: 10.3168/jds.2018-14438
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas fluorescens group bacterial strains are responsible for repeat and sporadic postpasteurization contamination and reduced fluid milk shelf life

Abstract: Postpasteurization contamination (PPC) of high temperature, short time-pasteurized fluid milk by gram-negative (GN) bacteria continues to be an issue for processors. To improve PPC control, a better understanding of PPC patterns in dairy processing facilities over time and across equipment is needed. We thus collected samples from 10 fluid milk processing facilities to (1) detect and characterize PPC patterns over time, (2) determine the efficacy of different media to detect PPC, and (3) characterize sensory d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 70 publications
1
56
0
Order By: Relevance
“…The efficacy of both approaches to acidification suggests that pH, rather than other fermentation-related changes in the milk, determines the ultimate appearance of the pigment. It is likely that modern high-temperature shorttime pasteurized milk appears gray when contaminated due to its near-neutral pH and its low prevalence of lactic acid bacteria that reach spoilage levels (i.e., reduce the pH) over shelf life (Reichler et al, 2018). By extension, it could be surmised that blue, rather than gray, pigment was produced on mozzarella cheese by these Pseudomonas because of the acidification of the cheese during production, having much the same ef-fect as has been reported in fluid milk.…”
Section: Some Pseudomonas Strains Can Cause Both Gray Color Defects Imentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of both approaches to acidification suggests that pH, rather than other fermentation-related changes in the milk, determines the ultimate appearance of the pigment. It is likely that modern high-temperature shorttime pasteurized milk appears gray when contaminated due to its near-neutral pH and its low prevalence of lactic acid bacteria that reach spoilage levels (i.e., reduce the pH) over shelf life (Reichler et al, 2018). By extension, it could be surmised that blue, rather than gray, pigment was produced on mozzarella cheese by these Pseudomonas because of the acidification of the cheese during production, having much the same ef-fect as has been reported in fluid milk.…”
Section: Some Pseudomonas Strains Can Cause Both Gray Color Defects Imentioning
confidence: 99%
“…This level of Pseudomonas can realistically be achieved in commercial fluid milk over 21 d of storage at refrigeration temperatures, particularly under conditions of slight temperature abuse. For example, Reichler et al (2018) observed that milk contaminated with Pseudomonas at the processing facility showed an average SPC of 8.23 log cfu/mL after 21 d of storage at 6°C.…”
Section: Some Pseudomonas Strains Can Cause Both Gray Color Defects Imentioning
confidence: 99%
“…The total bacterial count and TVBN value in Figure are very similar to those in Figure A and 4B (variance analysis showed no significant difference [ P > 0.05]), implying that P. fluorescens is the most important spoiler of tilapia fillets across all the storage temperatures investigated in this study (4, 0, and –3 °C). P. fluorescens has frequently been identified as one of the most dominant species in some animal foods, such as fish (Parlapani & Boziaris, ; Tryfinopoulou, Tsakalidou, & Nychas, ), milk (Reichler, Trmčić, Martin, Boor, & Wiedmann, ), beef (Chan, Joo, Faustman, Sun, & Vieth, ), and pork and poultry (Cheng, Doyle, & Luchansky, ). While Xie, Zhang, Yang, Cheng, and Qian () demonstrates that P. fluorescens displays strong spoilage activity in salmon at 4 °C, there are few reports on the spoilage activity of P. fluorescens at temperatures below 0 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the growing demand for extended shelf life (ESL) milk (12) imparts an additional hurdle for milk quality by increasing the period of time postpasteurization that the milk must remain of sufficient quality for consumption. Paenibacillus species isolates are frequently isolated from fluid milk (10,12,31), yet few studies have examined the genetic and phenotypic diversity among these isolates. To this end, we characterized a preexisting collection of 1,228 Paenibacillus species isolates collected from milk and dairy environments and found that P. odorifer is the predominant Paenibacillus sp.…”
Section: Discussionmentioning
confidence: 99%